Heritage Stone 1. Repair and Maintenance of Natural Stone in Historical Structures: The Potential Role of the IUGS Global Heritage Stone Initiative - Pereira, Dolores; Marker, Brian (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
Natural stone has been used for millennia in many historically and culturally important structures. It inevitably undergoes weathering from natural processes and damage from human activities. Deterioration affects both ornamental features and main structural members of constructions, ultimately requiring repair and maintenance, or causing loss of the structure altogether. Stone similar to the original should generally be used for repairs, but if that is impossible, a closely similar material is required. Use of inappropriate stone or treatment with incompatible mortars can be aesthetically unsightly or have structurally and financially damaging consequences. Such use typically arises because of a lack of information and awareness among commissioners and specifiers of works, along with budget constraints leading to selection of cheaper alternatives. Even some World Heritage Sites have suffered. Selected examples from Western Europe illustrate these problems. The Global Heritage Stone initiative has been launched to improve recognition of the internationally most important heritage stones, promote their proper use in construction, maintenance and repair, and to stress the need to safeguard important stone resources for future use.